2004
DOI: 10.1038/sj.leu.2403462
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal origin of separate evolution of leukemia in identical twins

Abstract: Several studies involving identical twins with concordant leukemia and retrospective scrutiny of archived neonatal blood spots have shown that the TEL-AML1 fusion gene in childhood acute lymphoblastic leukemia (ALL) frequently arises before birth. A prenatal origin of childhood leukemia was further supported by the detection of clonotypic immunoglobulin gene rearrangements on neonatal blood spots of children with various other subtypes of ALL. However, no comprehensive study is available linking these clonotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…5 Further evidence for an in utero leukemic transformation comes from the predominance of fetal type D-J joining of the immunoglobulin H (IgH) heavy-chain genes in young children with B-precursor ALL. 6,7 The detection of concordant leukemia in monozygotic twins, [8][9][10][11][12][13] strongly supports the hypothesis that leukemogenesis may be initiated in utero. The only plausible explanation for concordant leukemia in monozygotic twins is that the transformed cell in one twin spreads to the other twin, presumably by vascular anastomoses that exist within shared monochorionic placentas.…”
Section: Introductionmentioning
confidence: 59%
“…5 Further evidence for an in utero leukemic transformation comes from the predominance of fetal type D-J joining of the immunoglobulin H (IgH) heavy-chain genes in young children with B-precursor ALL. 6,7 The detection of concordant leukemia in monozygotic twins, [8][9][10][11][12][13] strongly supports the hypothesis that leukemogenesis may be initiated in utero. The only plausible explanation for concordant leukemia in monozygotic twins is that the transformed cell in one twin spreads to the other twin, presumably by vascular anastomoses that exist within shared monochorionic placentas.…”
Section: Introductionmentioning
confidence: 59%
“…Matigian et al (2007) used Pearson correlation as the similarity measure for hierarchical clustering of gene expression profiles in lymphoblastoid cell lines from three MZ twin pairs that were discordant for bipolar disorder, and found that the co-twins of all pairs clustered adjacently. Such high within-pair similarity in MZ pairs was not observed by Teuffel et al (2004), who subjected the bone marrow gene expression profiles of 33 children with acute lymphoblastic leukemia, including one pair of MZ twins concordant for the disease, to hierarchical clustering using Euclidean distances and applying the average linkage clustering algorithm. The authors noticed that the co-twins did not cluster adjacently and ascribed this effect to disease-related changes in gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] Unless the postnatal genetic hit(s) is inevitable, the prevalence of newborns harboring preleukemic first hit-cells should exceed the cumulative incidence of the corresponding leukemia. Accordingly, gene transcripts from the most common childhood ALL chromosomal translocation, t(12;21)(p13;q22)[ETV6-RUNX1], were demonstrated in approximately 1% of healthy newborns in one British study, 12 corresponding to 100-fold the cumulative incidence of ETV6-RUNX1-positive ALL in childhood.…”
Section: Introductionmentioning
confidence: 99%